SPATIAL AND TEMPORAL DISTRIBUTION OF NATURAL ENEMIES VISITING REFUGIA IN A PADDY FIELD AREA IN MALANG - Maisyaroh, Wiwin; Yanuwiadi, Bagyo; Leksono, Amin Setyo; PG, Zulfaidah (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Human activities in seeking agricultural lands, has change the traditional agricultural system into intensive cultivation system. One effort to minimize intensive agriculture system is the use of natural enemies to control pests. Habitat management should be implemented by creating habitat favored by natural enemies. This research aims to determine the spatial and temporal distribution of natural enemies of wild plants: Mimosa pudica, Vernonia cinera, Marsilea crenata, and Pistia startiotes on agricultural land. This research was conducted in March-April 2010 in Malang Sawojajar farmland. Plants placed in the corner field (refugia areas), visiting insects was observed starting from refugia areas and two meters away from the refugia area. Observations of insect use the